Optimization of Marine Activities Based on Spatial Regional Planning and Geographical Approaches: A Case Study of Tol Laut Program in Indonesia - Djunarsjah, Eka; Munaf, Dicky Rezaldy; Putra, Briantara Revidinda; Pamungkas, Bagaskoro; Roup, Gabriella Azzahra; Mirenza, Adinda Dheren; Wisayantono, Dwi; Julian, Miga Magenika; Muhammad, Fickrie; Putra, Andika Permadi; Lubis, Nafandra Syabana (Indonesian Journal of Geography, 2025)
Tol Laut is a marine activity that manages the maritime highway system in Indonesia to ensure and improve connectivity within the national logistics and supply chain system. This system arises because of the inequality of economic growth and development between several regions and provinces. The purpose of this program is to reduce high price disparities so that equity across regions can be achieved. However, this system has not run optimally. The performance of the program, which has entered its eighth year, is still less than 30%. Many problems arise that persist in causing the high price of goods. Hence, this study will identify the causes of the suboptimal Tol Laut by using spatial and geographic approaches on a sample of T-3 shipping route. Based on the spatial approach, it is found that the route is not optimal, so a strategy is obtained to create a new optimal route by producing a more efficient distance of 51,148 nm and a more effective time of 2 hours 18 minutes. Based on the geographical approach, the economic, social, and cultural factors that influence it were obtained. The identification of economic factors shows that high insurance premiums cause price disparities. Through this research, a strategy to produce more efficient and effective tariffs is obtained so as to reduce high disparities. This is important because Tol Laut is national strategic project that needs to be maintained.Received: 2024-04-30 Revised: 2025-08-15 Accepted: 2025-12-03 Published: 2025-12-04